Palatina Chroma Brown Dye Bottle - Science History Institute (2017)
Round glass bottle with glass stopper; label attached to front identifies manufacturer and contents (label has been waxed over); bottle is half full with original dye.
Keywords: Dye industry; Badische Anilin- & Soda-Fabrik; Textile industry; Dyes and dyeing